Regional cooperation on water and climate resilience: Somalia’s perspective - Afyare, Abdifatah Ahmed Ali (Edelweiss Applied Science and Technology, 2025)
This investigation examines the efficacy of regional cooperation strategies in enhancing water and climate resilience in Somalia, addressing the critical issue of inadequate collaborative frameworks that contribute to resource mismanagement and heightened vulnerability to climate change impacts. Employing a mixed-methods approach, the study collects both qualitative and quantitative data through stakeholder interviews, policy analysis, and environmental assessments, ultimately revealing that existing initiatives lack comprehensive integration and often fail to leverage local knowledge and practices effectively. Key findings indicate that fostering stronger regional partnerships and establishing inclusive governance models could significantly mitigate water scarcity and improve adaptive capacity against climate variability, which are crucial for public health. The significance of these findings extends to the field of healthcare, where the interplay between climate resilience and water resource management is critical for preventing waterborne diseases and ensuring access to safe drinking water, thus enhancing community health outcomes. The broader implications of this research highlight the necessity for international support and funding to reinforce cooperative frameworks, offering actionable insights for policymakers and health professionals aiming to address the nexus of environmental sustainability and public health within vulnerable regions. Through improved governance and resource sharing, this study underscores the potential for more resilient health systems in Somalia, ultimately contributing to a proactive approach in mitigating the impacts of climate change on population health.